Genetic profiling of basal cell carcinomas. (1st September 2019) - Reinders, M.G.H.C.; Cosgun, B.; Gijezen, L.M.C.; van Oosterhoud, C.N.; Kelleners‐Smeets, N.W.J.; Vermander, E.; Vreeburg, M.; Steijlen, P.M.; Mosterd, K.; van Geel, M.
Summary: Basal cell carcinomas (BCCs or "rodent ulcers") are the most common type of skin cancer and generally do not spread elsewhere on the body. They are not unusual in older people, but someone who develops lots of BCCs from an early age may have the rare genetic condition Basal Cell Naevus Syndrome (BCNS or "Gorlin syndrome"). Other clues to BCNS include an unusually shaped face, cysts in the jaw, and tiny irregularities on the palms and soles called palmar pits. The diagnosis is confirmed by testing DNA extracted from a blood sample. BCNS is caused by a mistake (mutation) in a gene called PTCH1 which is usually inherited from a parent, but occasionally develops for the first time in the embryo, in which case, the patient is described as mosaic because some body cells contain the mistake and some do not. Mosaic patients can be hard to diagnose because they tend to have a milder form of the condition (sometimes the only sign is a BCC developing in childhood) and the blood test may be negative for PTCH1 mutations. This paper, from Belgium and the Netherlands, describes two such patients: a 41 year old woman with BCCs on just one side of her body and no other features of BCNS and a 36 year old woman with BCCs, jaw cysts and palmar pits. In both patients the blood test was negative but PTCH1 mutations were found in all the BCCs tested. Confirming the diagnosis enabled the doctors to counsel these patients about possible complications of BCNS and the risk of passing it on to the next generation.